Classification of 3097 patients from the Japanese melanoma study database using the American joint committee on cancer eighth edition cancer staging system. Issue 2 (May 2019) - Fujisawa, Yasuhiro; Yoshikawa, Shusuke; Minagawa, Akane; Takenouchi, Tatsuya; Yokota, Kenji; Uchi, Hiroshi; Noma, Naoki; Nakamura, Yasuhiro; Asai, Jun; Kato, Junji; Fujiwara, Susumu; Fukushima, Satoshi; et al.
Highlights: New AJCC 8 th Edition Cancer Staging System was implemented in 2018. However, it has not been validated in an Asian melanoma population. AJCC 8 th staging system could efficiently classify our Japanese melanoma cohort. We should be careful in managing Stage III disease since the survival curves of the 8 th Edition staging were completely different from the 7 th Edition. Abstract: Background: The American Joint Committee on Cancer (AJCC) 8 th Edition Cancer Staging System was implemented in 2018; however, it has not been validated in an Asian melanoma population. Objective: The purpose of this study was to validate the new system using a cohort of Japanese melanoma patients. Methods: The AJCC 7 th and 8 th Editions were used for TNM classification of patients in a database established by the Japanese Melanoma Study Group. Patient data with sufficient information to be applicable to the AJCC 8 th staging were selected. The Kaplan–Meier method was used to estimate disease-specific survival and relapse-free survival. Results: In total, data for 3097 patients were analyzed. The 5-year disease-specific survival according to the 7 th and 8 th Edition staging system were as follows: IA = 98.5%/97.9%; IB = 95.4%/96.2%; IIA = 94.2%/94.1%; IIB = 84.6%/84.4%; IIC = 72.2%/72.2%; IIIA = 76.2%/87.5%; IIIB = 60.7%/72.6%; IIIC = 42.0%/55.3% and IIID = none/26.0%. The 5-year relapse-free survival according to the 7 th and 8 th Edition staging was as follows: IA = 94.5%/92.7%; IB = 85.4%/85.3%; IIA = 80.1%/79.4%; IIB = 71.4%/70.6%; IIC = 56.8%/55.7%; IIIA = 56.8%/69.4%; IIIB = 42.6%/56.8%; IIIC = 20.0%/33.3% and IIID = none/6.5%. Conclusion: The results show that new staging system could efficiently classify our Japanese melanoma cohort. Although there was no difference in Stage I and II disease between the 7 th and 8 th Edition systems, we should be careful in managing Stage III disease since the survival curves of the 8 th Edition staging were completely different from the 7 th Edition. Moreover, our results indicate that adjuvant therapies for Stage IIB and IIC should be developed, since the relapse-free survival for these stages were equivalent to Stage IIIA and IIIB, respectively.